Effect of Implementing Simulation Education on Health Care Worker Comfort With Nasopharyngeal Swabbing for COVID‐19. (2nd June 2020) - Mark, Michelle E.; LoSavio, Phillip; Husain, Inna; Papagiannopoulos, Peter; Batra, Pete S.; Tajudeen, Bobby A.
Abstract : Objective: To determine if rapid implementation of simulation training for the nasopharyngeal swab procedure can increase provider confidence regarding procedure competency. Methods: A simulation training exercise was designed as a departmental initiative to improve competency performing nasopharyngeal swabs during the COVID‐19 pandemic. Sixty‐one health care workers attended teaching sessions led by the Department of Otorhinolaryngology on proper nasopharyngeal swab technique. After a brief lecture, participants practiced their swab technique using a high‐fidelity airway simulation model. Pre‐ and postintervention self‐evaluations were measured via standardized clinical competency questionnaires on a 5‐point Likert scale ranging from "No knowledge, unable to perform" up to "Highly knowledgeable and confident, independent." Results: Forty‐six participants in this study submitted pre‐ and postintervention self‐assessments. Postintervention scores improved on average 1.41 points (95% CI, 1.10‐1.73) out of 5 from a mean score of 3.13 to 4.54 ( P <. 0001). This reflects a large effect size with a Glass's delta value of 1.3. Discussion: Lecture coupled with simulation‐based teaching can significantly improve health care workers' confidence in performing nasopharyngeal swabs. Proper training for frontline workers performing swabs for COVID‐19 is essential to improving testing accuracy and can be achieved in a simple and timely manner. Implications for Practice: To meet the testing needs of the growing pandemic, many health care workers who are unfamiliar with nasopharyngeal swabs have been asked to perform this test. Simulation‐based teaching sessions may improve health care workers' confidence and help prevent false‐negative results. This intervention is easily reproducible in any setting where frequent nasopharyngeal swab testing occurs. Level of Evidence/Study Design: Prospective cohort study.